Resolution of Digital Technology Patent Disputes in Indonesia: Case Analysis of Nokia and PT Bright Mobile - Regita Dwi Azzahra; Upik Mutiara; Amiludin (Paulus Law Journal, 2026)
he rapid development of digital technology has increased the economic value of inventions based on software, algorithms, and information technology systems, while simultaneously leading to a rise in patent disputes in Indonesia. Digital patents possess unique characteristics, as they are intangible, easily replicated, and frequently involve cross-border licensing arrangements, which complicates legal enforcement. This study aims to analyze the urgency of resolving digital patent disputes and to evaluate the effectiveness of dispute resolution mechanisms under Indonesian positive law. The research employs a normative juridical method using statutory and conceptual approaches, examining Law Number 13 of 2016 on Patents and its practical implementation. The analysis focuses on the patent dispute between Nokia Technologies OY and PT Bright Mobile Telecommunication. The findings indicate that litigation through the Commercial Court faces significant procedural and technical evidentiary challenges, resulting in ineffective dispute resolution. This study concludes that alternative dispute resolution mechanisms, particularly mediation and arbitration, are more suitable for digital patent disputes due to their efficiency, speed, and ability to preserve the economic value of inventions. Therefore, stronger legal policies and adaptive dispute resolution mechanisms are necessary to ensure legal certainty and support the development of digital technology in Indonesia.